Selenium in modern agriculture - Jia‐Qiang Huang; Zhao‐Hui Wang; Lv‐Hui Sun; Le‐Li Wang; Yu‐Long Yin (Modern Agriculture)
Abstract Selenium (Se) is a micronutrient necessary in small amounts for the proper organism functioning. Se‐rich agriculture, also known as special agriculture, has the potential to improve agricultural production and produce beneficial agricultural products. This review discusses the various applications of Se in agriculture, including animal husbandry, crop production and aquaculture. It covers Se metabolites, the function and regulation of selenogenomes and selenoproteomes of human and animal food and the recycling of Se in food systems and ecosystems. Finally, the review identifies research needs that will support the basic science and practical applications of dietary Se in modern agriculture.